Concept of Smart Electrohydraulic Press for Impulse Sheet Forming - Knyazyev, M.K.; Beerwald, Ch. (Металлофизика и новейшие технологии, 2016)
Electrohydraulic impulse sheet forming (EHF) method proved its high efficiency at pilot, small-batch, and middle-scale production conditions. As the latest achievement, multielectrode discharge blocks provide effective forming of the middle and large size sheet parts. However, wide application of EHF technology in industry is limited mainly by two problems: instability of impulse pressure fields and lack of literature as well as skilled EHF specialists. Now the problem of instability is solved by a qualified EHF specialist with intermediate disclosing of tooling, inspection of intermediate shapes of blank, making corrections in loading diagram (electrodes’ connections), and setting of new level of discharge energies. New approach to this problem includes solutions based on intellectual computer numerical control of EHF equipment: monitoring of intermediate shape of sheet blank after each discharge and making corrections of loading parameters for the next discharge till the final shape of part. Intermediate shape can be determined by measurements with special sensors built in a die in characteristic places (points). Another subsystem should analyse position of several principal segments of blank, compare them with total strategy of forming procedure for a definite type of sheet part, reveal those places, which need higher pressure to harmonise forming process, and give this information to the subsystem controlling a multicircuit current generator for optimised configuration of activated electrodes and energy level, thus, determining new pressure loading diagram for the next discharge. Now, the tests for blank shape measuring system are planned to solve this principal problem for realisation of the submitted concept. In addition, principal design solutions for multicircuit current generator with special unit for reconnections of electrodes are in work.